Palmitate-induced endothelial dysfunction is attenuated by cyanidin-3-O-glucoside through modulation of Nrf2/Bach1 and NF-κB pathways. Issue 3 (15th December 2015) - Fratantonio, D.; Speciale, A.; Ferrari, D.; Cristani, M.; Saija, A.; Cimino, F.
Graphical abstract: Highlights: Cyanidin-3- O -glucoside protects HUVECs from palmitic acid-induced injury. Cyanidin-3- O -glucoside inhibits palmitic acid-induced changes in cellular redox status. Cyanidin-3- O -glucoside inhibits endothelial activation induced by palmitic acid. Cyanidin-3- O -glucoside modulates the balance of Nrf2 versus Bach1 inside the nucleus so influencing upregulation of EpRE-mediated gene expression. Abstract: Free fatty acids (FFA), commonly elevated in diabetes and obesity, have been shown to impair endothelial functions and cause oxidative stress, inflammation, and insulin resistance. Anthocyanins represent one of the most important and interesting classes of flavonoids and seem to play a role in preventing cardiovascular diseases. Herein, we investigated the in vitro protective effects of cyanidin-3- O -glucoside (C3G) on cell signaling pathways in human umbilical vein endothelial cells (HUVECs) exposed to palmitic acid (PA), the most prevalent saturated FFA in circulation. Our data reported a significant augmentation of free radicals and oxidative stress in HUVECs exposed to PA for 3 h, while C3G pretreatment improved intracellular redox status altered by FFA. Moreover, C3G significantly inhibited NF-κB proinflammatory pathway and adhesion molecules induced by PA, and these effects were attributed to the activation of Nrf2/EpRE pathway. In fact, C3G induced Nrf2 nuclear localization and activation of cellular antioxidant and cytoprotective genes at baseline and after PA exposure in endothelial cells. Our data confirm the hypothesis that natural Nrf2 inducers, such as C3G, might be a potential therapeutic strategy to protect vascular system against various stressors preventing several pathological conditions.